Faktor yang Berhubungan dengan Nyeri Dismenore Primer pada Siswi di SMA Negeri 15 Semarang - Rohmawati, Wahidah; Wulandari, Dyah Ayu (Poltekkes Kemenkes Palu, 2019)
The result of interview with 10 students found that they have ever experienced (dysmenorrheal) they did not focus on teaching and learning until they asleep in the classroom and asked to permission to went home because unable to bear the pain that they feel, one of them rarely did physical activity such as sports, then they feel (dysmenorrheal) when menstrual, they also were burdened by tasks and routines of study, if they did examination. The purpose of this study was: to analyze the factors of primary dysmenorrheal on students at SMA Negeri 15 Semarang. This research was quantitative and it used cross-sectional method, the samples of this study were 138 respondents, and the researcher used proportionate stratified random sampling. The researcher also used chi-square test. The result of this study: it is shown that there was correlation between menarche with primary dysmenorrheal with evidence p-value <0,001, there were correlation between routinely of sport with primary dysmenorrheal with evidence p-value <0,001, there were correlation between stress with primary dysmenorrheal with evidence p-value <0,001. Recommendation: the teenagers are expected to increase sports activity and avoid stress so that can reduce the pain of dysmenorrheal.